Pengaruh Alokasi Dana Desa, Potensi Desa dan Kinerja Pemerintah Desa Terhadap Pemberdayaan Masyarakat - Aldita Henry Linda Setyawati; Indra Lila Kusuma; Maya Widyana Dewi (Jurnal Akuntansi dan Pajak, 2022)
ABSTRACT This study aims to examine the effect of village fund allocation, village potential, and village government performance on community empowerment. This type of research includes quantitative research using primary data obtained directly by respondents using a questionnaire. The population in this study is the community in Demangan Village. The method used in selecting the sample is purposive sampling and determining the sample based on the criteria set by the researcher. Respondents in this study were 96 respondents. Based on the results of primary data processing (questionnaire) with multiple linear regression analysis method, F test and T test, it is known that the village fund allocation variables, village potential, and village government performance simultaneously have a significant effect on community empowerment. Partially this research shows that the allocation of village funds, village potential has a significant positive effect on community empowerment. Meanwhile, the allocation of village funds does not have a significant effect on community empowerment. Keywords: village fund allocation, village potential, village government performance, community empowerment